Surface, microstructure, and tensile deformation characterization of LPBF SS316L microstruts micromachined with femtosecond laser. (15th November 2021) - Ghosh, Abhi; Biswas, Sanchari; Turner, Tiffany; Kietzig, Anne-Marie; Brochu, Mathieu
Graphical abstract: Highlights: For the first time, femtosecond laser micromachining has been utilized to eliminate the as-built surface roughness of LPBF fabricated microstruts, including its surface-associated microstructures. The femtosecond laser micromachining causes no significant microstructural damage at the surface and sub-surface of the microstruts. Micromachined microstrut tensile specimens experience a considerable enhancement in uniform tensile elongation in comparison to their as-built state. Micromachining-associated surface features affect the non-uniform tensile elongation; ablation-induced surface asperities evolve into notches and initiate the final failure. Abstract: Considerable surface roughness, dimensional deviation, and non-uniform microstructure are a few of the characteristics found on thin or micro-scale features fabricated via laser powder bed fusion (LPBF) that yield inferior and/or inconsistent mechanical properties. Femtosecond laser micromachining can aid in fabricating micro-scale parts with ultra-high dimensional precision. In this work, the surface and tensile behavior of microstruts of 500 μm nominal diameter micromachined with Gaussian laser pulses of < 100 f s duration are characterized. Roughness parameters such as R a = 0.9 ± 0.2 μm and R z = 3.4 ± 1.3 μm are achieved on the micromachined faces. Surface-associated grains are successfully ablated with negligible microstructural damage to the microstruts. As a result, the average uniform strain under quasi-static tensile loading is measured as 0 . 54 ± 0 . 02 compared to 0 . 42 ± 0 . 01 for the as-built microstruts. Uniform and non-uniform deformation strain portions are separated analytically and characterized primarily via in-situ imaging. Progressive degradation of the surface and dimensional variance is observed on the micromachined test specimens. Post necking initiation, ablation-associated asperities on the micromachined surfaces evolve into notches, leading to tensile failure.